PENGARUH SISTEM PENGENDALIAN INTERNAL, DISIPLIN KERJA, DAN EFEKTIFITAS SIA TERHADAP KINERJA KARYAWAN PADA UNIVERSITAS ISLAM KALIMANTAN MAB - Siti Mardah; Aida Vitria; Ana Sofia Herawati; Muhammad Arsyad; Muhammad Rindy; Muhammad Taufik (Politeknik Negeri Malang, 2026)
This study aims to demonstrate the influence of the Internal Control System (ICS), work discipline, and the effectiveness of the Accounting Information System (AIS) on employee performance at the University of Islam Kalimantan MAB. The research method employed is a quantitative causal-associative approach using saturated sampling. The results of the study indicate that simultaneously, SPI, work discipline, and AIS effectiveness have a significant influence on employee performance. Partially, work discipline and AIS effectiveness provide a significant positive contribution, while SPI shows a significant negative influence. This indicates that an overly rigid control system has the potential to reduce productivity due to psychological pressure.